Africa in the Changing World Development Paradigm - Vasilʹev, A. M. (Alekseĭ Mikhaĭlovich) (Book collections on Project MUSE., 2015)
The volume contains abstracts of papers presented at the 12th Conference of Africanists organized by the Institute for African Studies of the Russian Academy of Sciences in May 2011. The Conference, held triennially since 1969 is a major event in the area of African studies in Russia and beyond. What is particularly remarkable is the number and the diversity of the participants: academics, diplomats, Moscow-based and provincial as well as foreign participants from a staggering number of countries: Belgium, Brazil, Cameroon, Canada, Cote d'Ivoire, Czech Republic, Denmark, France, Germany, India, Italy, Kenya, Kazakhstan, Mozambique, Nigeria, Poland, Spain, South Africa, Sudan, Tanzania, Togo, UAE, UK, USA, Zimbabwe. Subjects covered range from economics, foreign relations, security issues, administration to history, culture, linguistics and religious studies. The book is a good reference tool to today's problematics in African studies as it presents a cross-section of this vast and diverse field. The Conference, held triennially since 1969 is a major event in the area of African studies in Russia and beyond. What is particularly remarkable is the number and the diversity of the participants: academics, diplomats, Moscow-based and provincial as well as foreign participants from a staggering number of countries: Belgium, Brazil, Cameroon, Canada, Cote d'Ivoire, Czech Republic, Denmark, France, Germany, India, Italy, Kenya, Kazakhstan, Mozambique, Nigeria, Poland, Spain, South Africa, Sudan, Tanzania, Togo, UAE, UK, USA, Zimbabwe. Subjects covered range from economics, foreign relations, security issues, administration to history, culture, linguistics and religious studies. The book is a good reference tool to today's problematics in African studies as it presents a cross-section of this vast and diverse field.